PENGARUH PERHATIAN ORANG TUA DALAM KEGIATAN BELAJAR TERHADAP HASIL BELAJAR FIQIH SISWA KELAS VIII MADRASAH TASNAWIYAH DARUL HIJROH POLOKARTO KABUPATEN SUKOHARJO TAHUN PELAJARAN 2021/2022 - Muhammad Arifin; Taufiq Usman; Jafar Nashir (Jurnal Ilmiah Hospitality, 2022)
One indicator of the success of the implementation of education is the high quality of the human resources produced. While one form of educational success can be seen from the success of learning. If learning goes well, it is expected that the learning outcomes achieved by students are also good. Learning is a conscious and planned effort to create a learning atmosphere and educational process so that students actively develop their abilities to have religious spiritual strength, self-control, character, intelligence, noble character, and skills needed by themselves, citizens, nation and country. Parents have a big share and role for the success of children's learning. Parents are not only as educators but also as mentors and also responsible for children. The responsibility of parents is not only to send their children to school but also to pay attention to their children's learning activities and activities at home. The purpose of this study was to determine the effect of parental attention on the learning activities of eighth grade students of Madrasah Tsanawiyah Darul Hijroh Polokarto, Sukoharjo Regency in the 2021/2022 academic year, to find out the learning outcomes of fiqh for eighth grade students of Madrasah Tsanawiyah Darul Hijroh Polokarto, Sukoharjo Regency, in the 2021/2022 academic year and to find out the influence of parental attention in learning activities on the fiqh learning outcomes of class VIII Madrasah Tsanawiyah Darul Hijroh Polokarto, Sukoharjo Regency, 2021/2022 Academic Year. This research method includes the research approach, time and place of research, population and research samples, data collection techniques, prerequisite tests and hypothesis testing. The results of this research are the attention of parents in the learning activities of class VIII Madrasah Tsanawiyah Darul Hijroh Polokarto is good with an average of 57.11 which is included in the interval 54 – 60. In the good category there are 46 students reaching 83.63%, in the category there are enough 6 students or reaching 10.90% and in the less category there are 3 students or reaching 5.45%, the fiqh learning outcomes of class VIII Madrasah Tsanawiyah Darul Hijroh students are good with an average of 89.31 which are included in the interval 88 - 95 In the good category there are 38 students reaching 69.09%, in the sufficient category there are 12 students or reaching 21.81% and in the less category there are 5 students or reaching 9.09% and in the empirical test obtained r count of 0.886 if consulted with r table 1% significance level is 0.265 and at 5% significance level is 0.224 means r count > r table table at 1% or 5% significant level. Thus the hypothesis that reads There is a significant positive influence between parental attention in learning activities on the learning outcomes of fiqh students of class VIII Madrasah Tsanawiyah Darul Hijroh Polokarto, Sukoharjo Regency, 2021/2022